Long Term Stability of Time Preferences and the Role of the Macroeconomic Situation - Hjördis Hardardottir (Lund University, School of Economics and Management, Department of Economics, 2016)
We look at the stability of survey based subjective time preferences over time using data from a Dutch panel survey with a long time horizon and find that the ranking of individual time preferences is stable. Simple observation of the aggregated measured time preferences reveals instability in aggregated preferences. In order to shed light on this instability we look at the relationship between the individual socio-economic situation and time preferences and the macroeconomic situation and time preferences. While we find no clear relationship between socio-economic situation and time preferences, we find that for the sample as a whole patience is positively correlated with economic growth, but negatively correlated with income inequality. When studying how the estimations differ across income groups we observe that there is a considerable asymmetry in how different income groups react to changes in the macroeconomic situation.
Keywords: D01; D63; J31; 330; Time preferences; stability of preferences; income inequality; economic growth; determinants of preferences